Sense of Justice, Trust, and Compliance: Evidence from Motor Vehicle Tax Penalty Removal in Jakarta - Riza, Fahrul; Pranoto, Henry Susanto; Anandatama, Dhika; Armando, Mochamad Gattan Farellio (Jurnal Manajemen Pelayanan Publik, 2026)
Tax compliance plays a crucial role in supporting regional fiscal capacity, yet motor vehicle tax compliance in Jakarta remains below optimal levels. To encourage taxpayers to settle arrears, the Jakarta Provincial Government implemented a temporary elimination of administrative penalties. This study examines how this policy interacts with taxpayers’ sense of justice and trust in the tax system to shape their intention to comply. Drawing on the Theory of Planned Behaviour, the research investigates whether fairness-based perceptions provide sufficient motivation for voluntary compliance and whether penalty relief enhances taxpayers’ perceived behavioural control. Using a quantitative approach, data were collected from 213 registered vehicle taxpayers and analyzed with PLS-SEM. The results show that a sense of justice significantly increases trust but does not directly increase compliance intentions. Trust also does not significantly influence compliance on its own. However, penalty elimination strengthens the effect of justice on both compliance and trust. Past compliance emerged as the strongest predictor of current compliance intention, underscoring the role of behavioral habit. These findings suggest that fairness establishes willingness to comply, but a conducive policy environment is essential for that willingness to manifest as action. Policy implications and future research directions are discussed.